Development of Child Protection Policy Against the Dangers of Sexual Predators - Ghafur, Fauzan; Kanggas, Fazari Zul Hasmi (Program Pascasarjana UIN Sumatera Utara, 2025)
The application of chemical castration punishment for sexual predators is an appropriate policy to protect children from sexual predators in Indonesia, as formulated in Article 81 and Article 81A of Government Regulation in Lieu of Law Number 1 Year 2016 on the Second Amendment to Law Number 23 Year 2002 on Child Protection. It is hoped that this policy can reduce the number of sexual violence that occurs in children. But there are polemics about the punishment, including; various groups think that castration punishment has violated human rights, the absence of technical instructions to perform chemical castration, to the rejection of the Indonesian Doctors Association (IDI) to become the executor of chemical castration because it is contrary to the medical code of ethics. This research has two problem formulations, namely; I) Why does the Government of Indonesia apply chemical castration punishment for sexual predators? II) How is the human rights perspective on chemical castration punishment? This research is a normative research with secondary data sources consisting of primary legal materials, secondary legal materials, and tertiary legal materials. Using data collection techniques with literature study and interviews. While data analysis uses qualitative analysis so that this form of research is evaluative research. The approaches taken are conceptual approach, legislative approach, and historical approach. The purpose of this research, namely; I) to explain more deeply the development of child protection policies in Indonesia until the implementation of chemical castration punishment. II) to explain further about human rights perspective towards chemical castration punishment. Finally, it concludes that: I) The implementation of chemical castration punishment by the Government of Indonesia is an effort to reduce the number of sexual violence against children. II) Chemical castration punishment in Indonesia is in accordance with the spirit of human rights in Indonesia. Because it can protect the human rights of children who range to be harmed.